CIRCULAR ECONOMY AND CREATE NEW VALUES - RECYCLING, RENEWABLE ENERGY, ECOLOGY - Đurić, Stanka; Stošić Mihajlović, Ljiljana; Trajković, Svetlana (Journal of process management and new technologies, 2017)
The waste is a global problem of the protection of the planet. It was established that the strategy of Serbia and the European Union (EU). No urban environment that is completely solved the problem of waste. These are the technologies that municipal waste is completely recycled to the useful value is returned to the industry which is becoming an economic resource. The development of new technology realizes a complete recycling of mixed municipal waste. Politics, local government and citizens are to such efforts need to be supported and implemented. Development Techno MBO-T technology to achieve the goals of sustainable development, circular economy is achieved and targets "zero waste". The construction of standard factories for processing and recycling of municipal waste can be achieved through economic, environmental, energy and social development goals Serbia.